Effect of ultra-mini percutaneous nephrolithotomy and ShuoTong ureteroscopy on the stress response, inflammatory indices, and urokinase level in patients with polycystic kidney disease complicated with renal calculus - Qiao, Du; Cheng, Luo; Xiaomei, Tian; Baolei, Shi; Yingyi, Li; Hui, Zhang; Shaohua, Bian; Wei, Liu; u, Dai Y; Fangqiong, Deng; Jie, Liu; Shuangning, Liu (Cellular and Molecular Biology, 2022)
This study aimed to explore the effects of ultra-mini percutaneous nephrolithotomy (UMP) combined with ShuoTong ureteroscopy on the stress response, inflammation indicators and urokinase levels in patients with polycystic kidney disease and kidney stones. In this study, 42 patients with polycystic kidney disease and kidney stones diagnosed and treated in our hospital from February 2018 to February 2021 were selected as the research objects. They were randomly divided into the control group and the study group, with 21 cases in each group, and the control group adopted Ultra-mini percutaneous nephrolithotomy treatment; the study group was combined with ShuoTong ureteroscopy on the basis of the control group, and compared and analyzed the stress response, inflammation indexes, urokinase level, renal function, complications and stone clearance rate of the two groups of patients. After treatment, the average operation time, channel establishment time, hemoglobin decline, number of puncture channels, and hospital stay in the study group were significantly shorter than those in the control group (P<0.05); after treatment, the reduction in CRP and PCT in the study group was significantly higher than that in the control group The increase of Ang I and Ang II in the control group was significantly lower than that in the control group (P<0.05); the improvement of PGE2, NO, and LPO levels in the study group was significantly higher than that in the control group after treatment (P<0.05); the study group TH, Cys- The levels of C and β2-MG were significantly lower than those of the control group; the UK levels of the study group were significantly lower than those of the control group (P<0.05); the complication rate of 14.29% in the study group after treatment was significantly lower than that of the control group 33.33%; the study group The stone clearance rate of 95.24% was significantly higher than that of the control group 80.95% (P<0.05). In general, UMP combined with ShuoTong ureteroscopy is used to treat polycystic kidney with kidney stones, accurately determine the tip position of the needle sheath, ensure that the needle sheath enters the collection system to adjust its position, reduce patient stress and inflammation, improve safety and feasibility, and is worthy of clinical practice Promote applications.